Miradas críticas a los biobancos de datos genómicos desde el sur II: hacia una negación de la fundamentación ética del Programa Nacional de Referencia y Biobanco Genómico de la Población Argentina (PoblAr) - Delvitto, Ailin; Petino Zappala, María Alejandra; Mallou, Carolina Ocampo; Pallitto, Nahuel; Lavagnino, Nicolás José (Revista Colombiana de bioética, 2024)
Purpose/Background. In line with trends in the Global North and assuming the paradigm of precision medicine and precision public health, in Argentina the National Genomic Biobank Reference Program of the Argentine Population (PoblAr) was recently approved. The program plans to obtain genomic, phenotypic and lifestyle data from different communities in Argentina for the diagnosis and treatment of various diseases. The purpose of this paper is to criticize the ethical foundation of the project. - Methodology/Approach. The ethical foundations of PoblAr are exposed and analyzed from two different, although complementary, ethical approaches: Responsible Research and Innovation (IIR) and Latin American Critical Ethics (ECL). - Results/Findings. The principles of the IIR and the ECL deny the ethical foundation of PoblAr. The project is not ethically justified neither in its formal aspects nor in its material aspects according to the proposed theoretical frameworks. - Discussion/Conclusions/Contributions. Before being grounded in ethics, PoblAr is based on a dominant colonizing morality. Responsible Research and Innovation and Latin American Critical Ethics are proposed for the ethical analysis of techno-scientific projects in Latin America.
Gesehen am 09.02.2026